Daily travel behaviors and transport mode choice of older adults in Mexico City. (October 2022) - Villena-Sanchez, Jessica; Boschmann, E. Eric; Avila-Forcada, Sara
Abstract: Our paper adds to the aging mobilities literature by addressing the need for more empirical studies in the Global South and utilizing the 2017 Household Origin-Destination Survey (HODS 2017) to broadly understand the mobility of older adults in Mexico City. We use descriptive statistics to reveal travel behavior patterns and construct a multinomial logit model to understand variations in mode choice of older adults in Mexico City. Our analysis does provide an emphasis on differences by income class, gender, and neighborhood level access to public transportation. Results uncovered transport-related inequalities as poorer older adults travel for longer periods of time compared to their wealthier peers. In terms of travel behaviors, we found that 40.5% of older adults reported using public and paid transit, 32% walked, 26.5% drove, and only 1.2% biked. Also, we learned that when older adults have access to good public transit infrastructure, they use it, regardless of car ownership status. Also, mobilities resulting from gender differences among older adults showed that older females are less likely to use structured public transit, walking, and biking in comparison to older males. Lastly we outline research limitations and recommendations for future transport policies.